Peptoid-based reprogrammable template for cell-permeable inhibitors of protein–protein interactions. Issue 40 (9th August 2021) - Fukuda, Yasuhiro; Yokomine, Marin; Kuroda, Daisuke; Tsumoto, Kouhei; Morimoto, Jumpei; Sando, Shinsuke
Abstract : A peptoid-based modular approach using oligo( N -substituted alanine) as a reprogrammable template enables independent optimization of N -substituents and facile development of cell-permeable inhibitors of protein–protein interactions. Abstract : The development of inhibitors of intracellular protein–protein interactions (PPIs) is of great significance for drug discovery, but the generation of a cell-permeable molecule with high affinity to protein is challenging. Oligo( N -substituted glycines) (oligo-NSGs), referred to as peptoids, are attractive as potential intracellular PPI inhibitors owing to their high membrane permeability. However, their intrinsically flexible backbones make the rational design of inhibitors difficult. Here, we propose a peptoid-based rational approach to develop cell-permeable PPI inhibitors using oligo( N -substituted alanines) (oligo-NSAs). The rigid structures of oligo-NSAs enable independent optimization of each N -substituent to improve binding affinity and membrane permeability, while preserving the backbone shape. A molecule with optimized N -substituents inhibited a target PPI in cells, which demonstrated the utility of oligo-NSA as a reprogrammable template to develop intracellular PPI inhibitors.